Could Hemingway Have Benefitted from a Neuro-Optometric Approach for His Multiple Brain Injuries? A Viewpoint. - Ciuffreda, Kenneth J.; Yadav, Naveen K. (Optometry & Visual Performance, 2024)
The writer Ernest Hemingway received at least nine documented traumatic brain injuries during his many career adventures. Here we speculate on the possible visual and related sequelae of these repeated injuries, their likely effect on his writing and productivity, and the impact that neurooptometry might have had on his overall healthrelated well-being.